The Chages in Sex Hormones in Female Working in Battries Manufacturing Plant - Mohammed A. Taher; Salim A.Hammadi; Ali A.Ali (College of Pharmacy University of Baghdad, 2017)
Lead has toxic effects on reproduction of both male and female.  It can cause decreased sex drive ,  infertility and abnormal menstrual cycle  in women.  This study was designed to evaluate the effect of exposure to lead in batteries female workers on sex hormones level in the serum.Thirty nine (39) female workers (volunteers) in Iraqi Batteries Manufacturing Plants, Al-Waziriya / Baghdad  were participated in this study. They are classified into 3 groups,  first group included fourteen (14) female that  have been employed for 1-7 years ,  second  group  included thirteen (13) female that have been employed for 8-14 years , third  group included twelve (12) female have been employed for15-22 years and and fourteen females were included as the control . Blood lead level, serum FSH, LH, prolactin and total testosterone  were measured and compared for all subjects.The results indicated that mean of blood lead levels (BLL), testosterone levels were highly significant in all worker groups compared to the control (p<0.005).Prolactin levels in group I and FSH in group III were significantly higher than that in control ( P< 0.005) and (P<0.05)  respectively.  LH levels  in groups II and III were significantly higher than that in control (P<0.05, P<0.005 respectively). High incidence of hirsutism (48%)  and   miscarriages (50%) were observed in worker groups compared to control (11%). The results indicated that there are hormonal changes in female workers exposed to lead  associated with increased incidence of hirsutism and miscarriages compared to non exposed females . Key words: Lead , Sex hormones hyperandrogenemia